2021
DOI: 10.1093/nar/gkab769
|View full text |Cite
|
Sign up to set email alerts
|

Identification of host tRNAs preferentially recognized by the Plasmodium surface protein tRip

Abstract: Malaria is a life-threatening and devastating parasitic disease. Our previous work showed that parasite development requires the import of exogenous transfer RNAs (tRNAs), which represents a novel and unique form of host–pathogen interaction, as well as a potentially druggable target. This import is mediated by tRip (tRNA import protein), a membrane protein located on the parasite surface. tRip displays an extracellular domain homologous to the well-characterized OB-fold tRNA-binding domain, a structural motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Indeed, the EMAPII domain of Arc1p (monomeric homolog of tRip) has a preference for yeast tRNA Met and tRNA Glu (Deinert et al, 2001 ) and participates in efficient glutamylation and methionylation in the cell. (Galani et al, 2001 ) On the contrary, the tRNA specificity of the tRip EMAPII ( H. sapiens tRNA Leu , Ser , Asn , Ala ) (Cela et al, 2021 ) does not correlate with the aaRSs found in the Q‐ and M‐ MSCs, suggesting that imported tRNAs play a role beyond their aminoacylation by ERS, MRS and QRS in Plasmodium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the EMAPII domain of Arc1p (monomeric homolog of tRip) has a preference for yeast tRNA Met and tRNA Glu (Deinert et al, 2001 ) and participates in efficient glutamylation and methionylation in the cell. (Galani et al, 2001 ) On the contrary, the tRNA specificity of the tRip EMAPII ( H. sapiens tRNA Leu , Ser , Asn , Ala ) (Cela et al, 2021 ) does not correlate with the aaRSs found in the Q‐ and M‐ MSCs, suggesting that imported tRNAs play a role beyond their aminoacylation by ERS, MRS and QRS in Plasmodium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…We have discovered the only example to date of an exogenous tRNA import pathway, summarized in Fig. 1 [1][2][3][4] . In Plasmodium, the malaria parasite, P. berghei sporozoites (the extracellular infective form of the parasite, Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1) and potentially best imported into the parasite. Interestingly, tRip does not bind to tRNAs in a sequence-dependent manner, but would rather recognize post-transcriptional modifications that modulate this interaction 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations